2002
DOI: 10.1053/jhep.2002.32673
|View full text |Cite
|
Sign up to set email alerts
|

Dose-dependent inhibition of hepatic fibrosis in mice by a TGF-β soluble receptor: Implications for antifibrotic therapy

Abstract: Transforming growth factor (TGF)␤

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(107 citation statements)
references
References 37 publications
5
101
0
1
Order By: Relevance
“…Soluble TGF-b receptors and soluble Tb-RII antibodies block hepatic fibrosis in animal models. [32][33][34] In this study, we demonstrated that EGCG dose dependently blocked TGF-b signaling in passaged HSC (Figure 1a). Further experiments revealed that EGCG had no effect on the secretion or activation of latent TGF-b1 (Figure 2a).…”
Section: Discussionsupporting
confidence: 53%
“…Soluble TGF-b receptors and soluble Tb-RII antibodies block hepatic fibrosis in animal models. [32][33][34] In this study, we demonstrated that EGCG dose dependently blocked TGF-b signaling in passaged HSC (Figure 1a). Further experiments revealed that EGCG had no effect on the secretion or activation of latent TGF-b1 (Figure 2a).…”
Section: Discussionsupporting
confidence: 53%
“…Further, the comparison of absolute expression of type I collagen mRNA and respective protein amount as assessed by Sirius red staining suggests a relatively greater reduction of collagen at the protein level after administration of sPDGFRb. This discrepancy was previously described in experiments investigating the inhibition of hepatic sPDGFRb inhibits hepatic fibrogenesis E Borkham-Kamphorst et al fibrosis by sTbRII 30 and might be due to the posttranscriptional regulation of collagen expression in cultured HSC. 44 We have not yet analyzed the impact of sPDGFRb with regard to chemotaxis of HSC towards BD structures that were shown to contribute to the development of periductular fibrosis in cholestatic disorders.…”
Section: Discussionmentioning
confidence: 70%
“…For application of purified soluble receptor proteins (sTbRII, sPDGFRb), 25 mg/animal (0.1 mg/kg sPDGFRb inhibits hepatic fibrogenesis E Borkham-Kamphorst et al body weight) was administered intravenously upon bile duct ligature (BDL) according to established protocols. 30 Injections into the peritoneum were repeated twice a week until the animals were killed 14 days after surgery.…”
Section: Experimental In Vivo Model Of Liver Fibrogenesismentioning
confidence: 99%
“…13 Moreover, anti-TGF-β2 antibody and a TGF-β1 antisense oligonucleotide attenuate kidney fibrosis in the diabetic rat and in unilateral ureteral obstructions, respectively. 88,93 Hepatic fibrosis in rodents can be inhibited by soluble TβRII administered intraperitoneally 94 or by intramuscular injections of an adenovirus expressing the ectodomain of TβRII fused to the Fc portion of IgG. 95 Adenoviral soluble TβRII can also inhibit constrictive remodeling after coronary angioplasty in pigs.…”
Section: Antagonists Of Tgf-β For Disease Treatmentmentioning
confidence: 99%